Traditional Market Existence, Retribution Governance, and Trader Welfare: Evidence from Indonesia - Muhamad Juaini; Agus Riswanto (JMET: Journal of Management Entrepreneurship and Tourism, 2026)
Traditional markets are vital socio-economic infrastructures for small traders in developing economies, but their contribution to welfare depends on governance quality rather than physical presence alone. Drawing on institutional governance and service reciprocity perspectives, this study examines how traditional market existence and market retribution governance influence trader welfare at Montong Beter Market, East Lombok Regency, Indonesia. A quantitative explanatory survey was conducted among 78 permanent traders selected through simple random sampling from a population of 366 traders. Data were collected using a structured questionnaire and analyzed through descriptive statistics, classical assumption testing, and multiple linear regression. The model was significant, F(2, 75) = 38.877, p < .001, explaining 50.9% of the variance in trader welfare (adjusted R² = .496). Market retribution governance had a positive and significant effect on trader welfare (B = .670, β = .616, t = 6.393, p < .001), whereas traditional market existence showed a positive but non-significant effect (B = .170, β = .157, t = 1.629, p = .107). These findings indicate that the physical continuity of a traditional market does not automatically improve trader welfare when services, infrastructure, and accountability remain weak. Instead, welfare is more strongly associated with transparent, fair, predictable, and service-oriented retribution governance. The study contributes to market-governance literature by reframing market retribution as a reciprocal governance mechanism rather than a fiscal extraction instrument. It offers policy implications for enhancing trader welfare through transparent fee collection, visible reinvestment, sanitation improvement, spatial order, and participatory market management.